(untitled) (Development Service Industry Management, 2024)
In the course of writing the article, theoretical aspects and the general concept of creative management and its importance for modern enterprises were carefully considered, especially in the context of an unstable economic environment and the need for innovative development. The article systematizes the importance of integrating creative management into the management practices of enterprises, arguing its role in maintaining business competitiveness and stability. During the research, the existing tools of creative management, which are used for effective personnel management in modern enterprises, were analyzed in detail. It was determined that the use of these tools allows enterprises to ensure the necessary level of flexibility and adaptability in the management of tasks and projects. The main advantages of digital platforms in the context of structuring work processes and the integration of other tools for exchanging ideas have been summarized. Various platforms have also been systematized to improve communication and collaboration among staff, which contributes to effective information exchange and prompt resolution of tasks. Special attention was paid to talent management tools that help create a stimulating environment and support the career growth of employees. In addition, platforms for the organization of training and staff development are characterized, which contribute to the development of creative thinking and increase the motivation of employees. Based on the results of the study, recommendations were formulated for the implementation of these tools to strengthen the competitiveness of enterprises and support their innovative development.